2008
DOI: 10.1080/00207450701769323
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Selective Nature of Sensory Nerve Stimulation Using Different Sinusoidal Frequencies

Abstract: This study examines the ability to selectively activate different nerve fibers in a finger by using different sinusoidal stimulation frequencies. Specifically, the stimulation of A-beta, A-delta, and C-fibers is looked into, and responses from each of three different stimuli (5 Hz, 250 Hz, and 2000 Hz) are compared. Action potential (AP) responses from the different nerve fibers are simulated. Activation thresholds are determined for each fiber type. The resulting firing frequencies are compared with threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…A similar strategy may be useful for the retina as well. While the threshold differences measured physiologically and calculated in our models were in response to short duration pulses, other stimulus waveforms have begun to be evaluated [33; 34]. A more complete understanding of the activation process will enable accurate computational evaluation so that a wide range of stimulus waveforms and parameters do not have to be evaluated physiologically in order to optimize stimulation methods.…”
Section: Discussionmentioning
confidence: 99%
“…A similar strategy may be useful for the retina as well. While the threshold differences measured physiologically and calculated in our models were in response to short duration pulses, other stimulus waveforms have begun to be evaluated [33; 34]. A more complete understanding of the activation process will enable accurate computational evaluation so that a wide range of stimulus waveforms and parameters do not have to be evaluated physiologically in order to optimize stimulation methods.…”
Section: Discussionmentioning
confidence: 99%
“…The use of more complex stimulus waveforms is currently being explored to determine if they can provide better selectivity over conventional pulsatile stimuli (Langille et al 2008; Cantrell and Troy 2009; Freeman et al 2010c; Foutz and McIntyre 2010). For example, a recent study found that low frequency sinusoidal waveforms (10–25Hz) produced robust synaptic responses (i.e.…”
Section: The Response Of Retinal Neurons To Electric Stimulationmentioning
confidence: 99%
“…The use of alternative stimulation waveforms (i.e., nonpulsatile) for electric stimulation has not been well explored (but see also Cantrell and Troy 2009;Langille et al 2008). This may be caused in part by the early successes of pulsatile stimulation in cochlear implants and DBS for Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%